Ród Wierzbnów herbu Jastrzębiec w średniowiecznych księgach sądowych - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The author presents the chivalric family of Wierzbna of the Jastrzębiec coat of arms, drawing on the surviving medieval court registers. The available court registers from the 14th and 15th centuries make it possible to imagine the functioning of medieval chivalry in legal terms. The picture presented by the author fully corresponds generalisations, to the available information about other chivalric families, an assertion backed by over 700 pages of the author’s analyses of similar cases in courts of the provinces of Małopolska, Wielkopolska or Kujawy and Łęczyca. The court registers from Małopolska include a variety of judgements in property, personal or criminal matters. We find here disputes over estate division, debt settlement, seeking justice after assaults, scuffles or murders. There are many cases concerning debt, some involving Jewish bankers, problems with guarantees etc. The cases involve entire families, sons sue their fathers and there are also cases involving women, who became legitimate parties in legal relations and who pursued their claims to e.g. dowry and bridewealth. This affected particularly Tomek of Karwin, who had six daughters of marriageable age and no male heir, as a result of which his estates passed to the House of Masłowski of the Wieniawa coat of arms
Keywords: średniowiecze; ród Wierzbnów; księgi sądowe; rody rycerskie; rycerstwo